2D-OPC Subarray Structure for Efficient Hybrid Beamforming over Sparse mmWave Channels. (15th June 2021) - Yoo, Junhyuk; Sung, Wonjin; Kim, In-Kyung
Abstract : Millimeter-wave (mmWave) communication is a key technology of 5G new radio (NR) mobile communication systems. Efficient beamforming using a large antenna array is important to cope with the significant path loss experienced in the mmWave spectrum. The existing fully digital beamforming scheme requires a separate radio frequency (RF) chain for each antenna, which results in an excessive hardware cost and consumption power. Under these circumstances, hybrid beamforming which approaches the performance of fully digital beamforming while reducing the complexity is a promising solution for the mmWave multiuser transmission. By extending the existing hybrid beamforming strategies, this paper proposes a novel architecture which effectively reduces the hardware cost and complexity for large antenna arrays. The proposed scheme includes multiple subarrays in the form of uniform planar array (UPA) which are allowed to be overlapped in the two-dimensional space. The corresponding antenna structure is referred to as the two-dimensional overlapped partially connected (2D-OPC) subarray structure. We evaluate the performance of the proposed scheme to suggest performance-complexity trade-offs in designing versatile antenna arrays for efficient beamforming over the mmWave channel.